Immunology - Male, David K. , 1954- (Edinburgh, Scotland : Elsevier/Saunders, 2013)
This textbook teaches the basic and clinical immunology concepts
1. Components of the immune system -- 2. Modes of immune response -- 3. Defense against infectious agents -- 4. Immune responses against tissues -- 5. Hypersensitivity
"Student Consult"--Cover
Includes bibliographical references and index
Keywords: Immunology; Immune System; Immunity